The jetsetters : a novel - Ward, Amanda Eyre, 1972- (Ballantine Books, 2020)
"When seventy-year-old Charlotte Perkins submits a sexy essay to the "Become a Jetsetter" contest, she dreams of reuniting her estranged children: Lee, an almost-famous actress; Cord, a handsome Manhattan venture capitalist who can't seem to find a bride; and Regan, a harried mother who took it all wrong when Charlotte bought her a Weight Watchers gift certificate for her birthday. Charlotte yearns for the years when her children were young and she was a single mother who meant everything to them. When she wins the cruise, the family packs all their baggage--literal and figurative--and spends ten days traveling from sun-drenched Athens through glorious Rome to tapas-laden Barcelona on an over-the-top cruise ship, the Splendido Marveloso. As lovers new and old join the adventure, long-buried secrets are revealed, and the Perkins family is forced to confront the defining choices in their lives. Can four lost adults find the peace they've been seeking by reconciling their childhood aches and coming back to each other? In the vein of The Nest and The Vacationers, Ward has created a delicious and intelligent novel about the courage it takes to reveal our true selves, the pleasures and perils of family, and how we navigate the seas of adulthood to cruise--we can only hope--toward joy"--